EFEKTIVITAS DANA ZAKAT PRODUKTIF BERBASIS MASJID DALAM MENINGKATKAN KESEJAHTERAAN MUSTAHIK: (The Effectiveness of Mosque-Based Productive Zakat Funds in Improving the Welfare of Mustahik) - Wahyu Bagja Sulfemi; Ridwan Hardiansyah; Agus Priatna; Zaenal Abidin Riam (Raqib: Jurnal Studi Islam, 2025)
This study aims to analyze the effectiveness of mosque-based productive zakat management in improving the welfare of mustahik, with a case study at Baitul Mal Masjid (BMM) Al-Amin, Kavling Panorama, Sindang Barang, Bogor City. Productive zakat is viewed as a strategic instrument for empowering the Muslim community, serving not only as consumptive assistance but also as a sustainable means to promote economic independence. The research employed a qualitative descriptive-analytical approach, with data collected through in-depth interviews, observation, and documentation. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, presentation, and conclusion drawing. The findings indicate that BMM Al-Amin implements four main strategies in managing zakat funds: collection, management, distribution, and supervision. The funds are allocated for education, health, and productive business financing through an interest-free (qardhul hasan) scheme. This approach increased mustahik income by up to 35% within the first three months while strengthening their social and spiritual participation in mosque activities. Beyond economic outcomes, the program also enhanced public trust and social solidarity among congregants. Despite challenges such as limited funds, repayment delays, and low financial literacy, BMM Al-Amin demonstrates transparent, participatory, and value-based governance. The study concludes that mosques have significant potential to function as effective, equitable, and sustainable centers of community economic empowerment.